Fatal colon rupture by compressed air of high-pressure pump - Hinnawi, Sarah Al; Akarte, Dinesh S; Kude, Rajesh P (Journal of Indian Academy of Forensic Medicine, 2019)
Compressed air is the air which is kept at pressure higher than atmospheric pressure. It is mainly used in industries and garages and its  injudicious use can be dangerous. Sudden trans-anal insufflation of high amounts of compressed air may cause rupture of rectum,  intestines along with damage to other internal organs. It may be a used as a means of torture or causing homicide Limited literature on  the subject mostly reports fatal outcome. We report a rare case of accidental prank that went terribly wrong and led to the death of a  young man. The case report also discusses the mechanisms which may have led to death.
Keywords: Colon rupture; Compressed air; Barotrauma